Punitive turn or punitive imperialism?: analyzing the transformation in the Ecuadorian penal realm - Aguirre, Martha Vargas (Punishment in Latin America, 2025)
Criminological research, particularly in the Anglo-Saxon academic realm, has extensively examined the sharp increase in incarceration rates since the mid-1970s. Referred to as the “sociologies of the punitive turn” (Carrier, 2010), these studies argue that this surge reflects a sudden and harsh transformation in the logic governing penal practices and discourse. Some findings even suggest that this punitive shift has a global reach, impacting regions like Latin America. This broader narrative prompts an inquiry into whether a similar punitive turn occurred in Ecuador, a South American nation. Examination of prison demographics and legal frameworks in this country reveals a notable increase in incarceration rates during the 1990s, closely linked to drug trafficking control policies led by the United States. Consequently, I suggest that while the influence of neoliberal rationality, characteristic of the punitive turn, is evident, it’s more aptly described as a manifestation of punitive imperialism. Thus, it is imperative to analyze shifts in punishment trends within the framework of imperial dynamics, particularly considering the economic dependency of peripheral countries.